HEALTH EDUCATION AND CARE PRACTICES IN THE CONTEXT OF PREVENTABLE DISEASES - Freitas Macedo, Sthélio; Nelson Martins Júnior, Leonidas; da Silva Izidoro, Jaqueline; Islândia Barbosa Dantas de Meneses, Uberlândia; Kelly Neto Santos, Bruna; Andrade Virginio de Oliveira, Annelissa; Lídia Coutinho dos Santos, Ana; Maria da Silva, Josefa; de Cássia Tavares da Fonseca, Leila (Revista Gênero e Interdisciplinaridade, 2026)
Health education has become an essential strategy for tackling preventable diseases within the context of the Brazilian Unified Health System (SUS). This article presents a narrative literature review to analyze how educational practices have been mobilized as an instrument of care and prevention, especially in territories marked by social vulnerabilities. National studies published in the last ten years were analyzed, with an emphasis on intersectoral experiences, participatory methodologies, and pedagogical devices aimed at health promotion. The findings were organized into two categories: (1) health education and the prevention of preventable diseases in the SUS and (2) interfaces between public policies, territories, and care. It was observed that educational practices planned and sensitive to local contexts contribute to strengthening primary care, empowering individuals, and promoting health equity. However, challenges such as policy discontinuity, insufficient professional training, and fragmentation of actions still persist. It is concluded that health education, beyond the transmission of information, should be understood as a dialogical, emancipatory, and intersectoral process, capable of generating transformations in the living and health conditions of the population.